2012
DOI: 10.1017/s1355617711001883
|View full text |Cite
|
Sign up to set email alerts
|

The Ecological and Construct Validity of a Newly Developed Measure of Executive Function: The Virtual Library Task

Abstract: Virtual reality (VR) assessment paradigms have the potential to address the limited ecological validity of pen and paper measures of executive function (EF) and the pragmatic and reliability issues associated with functional measures. To investigate the ecological validity and construct validity of a newly developed VR measure of EF, the Virtual Library Task (VLT); a real life analogous task--the Real Library Task (RLT); and five neuropsychological measures of EF were administered to 30 patients with traumatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 48 publications
4
61
0
6
Order By: Relevance
“…The BADS aimed to measure executive functioning in a more ecologically valid way. A previous study confirmed that the MSET, one of the subtests of the BADS, was able to predict everyday executive functioning, suggesting that it is an ecologically valid tool (Renison, Ponsford, Testa, Richardson, & Brownfield, 2012). Nonetheless, in the present study, we did not find significant correlations between the MSET and the self-report questionnaire, the EFI-NL.…”
Section: Discussionsupporting
confidence: 73%
“…The BADS aimed to measure executive functioning in a more ecologically valid way. A previous study confirmed that the MSET, one of the subtests of the BADS, was able to predict everyday executive functioning, suggesting that it is an ecologically valid tool (Renison, Ponsford, Testa, Richardson, & Brownfield, 2012). Nonetheless, in the present study, we did not find significant correlations between the MSET and the self-report questionnaire, the EFI-NL.…”
Section: Discussionsupporting
confidence: 73%
“…Grupos con perfiles parecidos obtienen resultados similares en las tareas realizas virtualmente y su equivalente real, de lo que deducen que la tarea virtual es muy similar a la real. Concluyen que la validez ecológica del test como evaluador de las funciones ejecutivas es similar al de otro test tradicional, pero como la ventaja de que aporta una medida objetiva de las componentes cognitivas [Renison:2012].…”
Section: "Virtual Library"unclassified
“…Entre los sistemas revisados, son comunes los que utilizan una pantalla sencilla como soporte para la visualización del entorno, como son monitores LCD, televisiones o incluso la propia pantalla de un ordenador portátil [Edmans:2007], [Edmans:2009], [Katz:2005], [Navarro:2013], [Renison:2012], [Krch:2013], [Cao:2010], [Werner:2009], [Vourvopoulos:2014], [Dores:2012]. El uso de proyectores, permite visualizar el entorno en un mayor tamaño.…”
Section: Dispositivos De Visualizaciónunclassified
See 2 more Smart Citations